BAHASA MATEMATIKA SEBAGAI STRATEGI RETORIS DAKWAH DIGITAL: ANALISIS METAFORA KONSEPTUAL PADA KONTEN TIKTOK - Insani, Camelya Nurul; Ramadhan, Salbana Ziadatul; Sri Rahayu, Alleya Danti; Al Aziz, Fathurrohman; Pertiwi, Attin Rahmah; Putri, Amalia Azizah; Huda, Shohibul; Nurdiansyah, Muhamad Iqbal; Sulistyani, Anjar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the use of mathematical language as a creative communication strategy in Islamic da'wah content on social media, particularly TikTok, among Generation Z audiences. Using a qualitative descriptive approach with qualitative content analysis based on Krippendorff's (2019) framework, this research examined seven TikTok uploads that explicitly employed mathematical terms or symbols (numbers, arithmetic operators, or words such as